Clinical Treatment Prescription in Physiotherapy: A Scoping Review of Conceptual and Operational Parameters - Hernandez, Gustavo-Argenis; Salazar, Job (European Scientific Journal, ESJ, 2026)
Background: Treatment prescription constitutes a fundamental component of physiotherapy practice because it guides the planning and implementation of therapeutic strategies aimed at maintaining, improving, or restoring human movement and function. Despite its frequent use in clinical and academic contexts, the conceptual and methodological elements that define treatment prescription in physiotherapy remain inconsistently described in the literature. Purpose: This scoping review aimed to map and analyse the available scientific literature addressing the notion of clinical treatment prescription in physiotherapy, with particular attention to how prescriptions are defined and whether operational parameters required for reproducible implementation are reported. Methods: The review followed the reporting framework of the Preferred Reporting Items for Systematic Reviews and Meta-Analyses Extension for Scoping Reviews (PRISMA-ScR). A comprehensive search was conducted in PubMed/MEDLINE, Scopus, Web of Science, PEDro, OTSeeker, and Google Scholar, complemented by additional searches in books, book chapters, and institutional policy documents. Sources were eligible if they explicitly addressed the concept or definition of treatment prescription in physiotherapy. Results: A total of thirty-seven (n=37) records were identified. After the screening process, only one source met the predefined eligibility criteria. This document provided a conceptual definition of prescribing in physiotherapy practice but did not describe detailed operational parameters for implementing clinical prescriptions. Conclusions: The findings indicate that explicit and operational definitions of treatment prescriptions are rarely reported in physiotherapy literature. Greater conceptual clarity and clearer reporting standards are necessary to support the reproducibility of interventions and strengthen evidence-based physiotherapy practice.